Social benefits of clean energy: Evidence from Bangladesh - Mohammed Gazi Salah Uddin; Chowdhury Abdullah-Al-Baki; Donghyun Park; Ali M. Ahmed; Shu Tian (Asian Development Bank (ADB), 2023)
Solar adoption exploded until 2015 in Bangladesh, setting a precedent for electrifying previously unconnected areas worldwide. This study tries to measure the welfare effects of solar adoption using the three rounds of the Bangladesh Integrated Household Surveys. We applied both ordinary least squares and propensity score matching techniques to estimate the welfare effects of solar adoption. We found that solar adoption is associated with higher income, expenditure, and asset value growth, and a massive reduction in kerosene expenditure than non-adopters. Other findings include that solar households tend to abandon sharecropping in favor of trading and poultry farming, and that children in solar households benefit in terms of schooling and nutrition.
Keywords: O13; Q42; D12; O55; 330; energy transition; solar adoption; education; welfare; Bangladesh